The Pragmatics of Title and Address in Kurdish language - Kemal, Diyar A.; Ali, Talib H. (Humanities Journal of University of Zakho, 2018)
The paper attempts to shed lights on address and title terms in Kurdish language, it also describes and analyses pragmatically the semantic changes on lexemes and terms. The paper consists of three parts, apart from introduction and conclusion. The first part generally describes title and address, it also describes certain topics relating to semantics deixis, types of social deixis , title and noun and address and noun. The second part analyses semantically titles and address terms, it also draw a distinction between titles, address and nicknames. The third part focuses on metaphorical use of title and address, it highlights the metaphorical expressions that do not match with dictionary entries. The paper also attempts to identify title address movement, i.e. it focuses on those lexemes and terms that lost their semantic values and gains their pragmatic ones (honorific and derogatory). Finally the paper tackles cases where lexemes, title and address become proper name. The paper ends with conclusions followed by a list of references.